Pengaruh Sistem Organisasi Terhadap Motivasi Kerja Guru Pada Sekolah Menengah Kejuruan Negeri di Provinsi Jambi - Istikomah, Istikomah Istikomah; Masriani, Masriani; Prasetyo, Muhammad Anggung Manumanoso (NUR EL-ISLAM : Jurnal Pendidikan dan Sosial Keagamaan, 2020)
Every organization is basically a kind of control system. An irregular organizational system will have a negative impact and lack of control over the performance of the members of the organization. The organizational system also plays a significant role in creating a conducive atmosphere in the school environment. An effective and structured organizational system will provide boundaries and positive direction in the organization. This research is a quantitative research with survey method. From the results of this study it was found that the organizational system significantly influenced the work motivation of teachers in state vocational high schools Jambi Province. Based on the calculation results obtained by the analysis of the value thitung (9,0)> ttabel (1,969), until H0 is rejected and H1 is accepted. This means that the organizational system that is run and maintained within a school organization will be able to provide a significant influence on teacher work motivation. The research implications of these findings explain that the better the organizational system built in this school the better the effect will be on increasing teacher work motivation.